Misperceptions about Tax Audits - Bérgolo Sosa, Marcelo (2018)
For some entities, the utility-maximizing evasion rate depends substantially on tax audit features, such as audit probabilities and penalty rates. Bergolo et al. (2017) document large misperceptions about these features. In this paper, we expand the analysis of survey data to explore potential sources of these misperceptions. Of all the channels that we explore, recent contact with audits best explains differences in misperceptions.